Folleto: Qué son los mecanismos para compartir beneficios? - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2013)
Mechanisms for Sharing Benefits, or MCB, seek to redistribute equitably, among all users, the benefits of water gives us a basin preserved. The MCB are aimed at creating a virtuous circle between the welfare of the people and ecosystems in which they live.